Use of sea water for dyeing wool with reactive dyes - Ristić Nebojša; Mičić Aleksandra; Ristić Ivanka; Marković-Nikolić Dragana; Zdravković Aleksandar (Tekstilna industrija)
The high consumption of water and chemicals in textile dyeing conditions the development and promotion of alternative procedures that are environmentally safe and sustainable. Fresh water is an increasingly scarce natural resource, and its possible substitution with sea water would be a sustainable technological solution from the point of view of ecology. In this work, woolen fabric was dyed with reactive Lanasol and Drimalan F dyes in simulated and real seawater and the results were compared with the results of dyeing in distilled water. No sodium sulfate was added to the simulated seawater and real seawater dye baths. Samples dyed in seawater have more intense colors, good uniformity and excellent fastness to washing compared to the conventional process.